Pembauran Budaya Dalam Penyajian Kesenian Ronggiang Di Padang Tujuah Kanagarian Aua Kuniang Pasaman Barat - Rahmat Adriyanto; Afifah Asriati; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2019)
This article aims to describe the mixing of cultures in the presentation of Ronggiang art in West Pasaman, especially in the Kanagarian Tujuah Padang Aua Kuniang. The type of this research was qualitative research and used descriptive methods. The main instrument in the research was the researcher himself and was supported by supporting instruments such as stationeries, video camera and audio recorder. Data collection techniques were conducted by means of library research, observation, interviews, and documentation. The data analyzed was carried out by the steps of data collection, data reduction, data presentation and conclusion. The results indicated that the mixing of cultures in Ronggiang arts was that Ronggiang's arts could be enjoyed by tribes who had already located and became residents of the West Pasaman or specifically in Kanagarian Aua Kuniang. The three tribes that are currently residents of West Pasaman are derived from three cultures in Ronggiang art. The cultural elements that assimilate in Ronggiang dance are Malay, Minang and Javanese cultures. These cultures are not packaged into one dance project, Ronggiang art in Kanagarian Aua Kuniang. The impact of cultural assimilation in Ronggiang art has caused Ronggiang's art to survive in the lives of the Kanagarian Aua Kuniang community.